Determination of antimicrobial activity and some biochemical properties of honey and propolis in Turkish markets - Gür, Nazmi; Bayrak, Neval; Topdemir, Aykut (Progress in Nutrition, 2020)
Humans have consumed bee products for thousands of years due to their numerous health benefits. Honey is an invaluable substance made of a combination of nectar and pollen collected by bees from flowers. Honey contains carbohydrates, organic acids, proteins, amino acids, vitamins and minerals. It has been used as an effective medicinal product since ancient times for the treatment of skin burns, wound ulcers tumours and gastrointestinal disorders as well as an antibacterial and antifungal agent (1,9).Propolis, also referred to as bee glue, is a resinous hive product made of substances that honey bees collect from various plant sources and then mix with their own saliva and beeswax. Propolis contains various chemical compounds such as polyphenols, terpenoids, steroids, coumarin, amino acids and inorganic compounds (10-11).Despite the fact that propolis has been known since ancient times, it has become the focus of great interest in recent years as a useful substance in medicines and cosmetics. Propolis exhibits antibacterial, antifungal, antiviral, antioxidant, antitumor and anti-inflammatory activities (12,18).The composition of honey and propolis vary based on their plant origin (11-19); therefore, the aim of this study was to examine the natural microflora, antimicrobial effect and total protein and fatty acid contents of five types of honey and five types of propolis sold in Turkish markets.